Pertanggungjawaban Pidana Dokter Militer di Bidang Hukum Kesehatan: Criminal Liability of Military Doctors in Health Law - Atmaja, Ayu Indra Atryadi; Sutarno, Sutarno; Pramono, Pramono (Jurnal Hukum dan Etika Kesehatan, 2025)
There are complex issues concerning criminal acts and the criminal liability of military doctors within the scope of health law. Military doctors serve dual roles: as healthcare providers and as members of the military. When a military doctor commits a crime in the context of health services, they act as a doctor. However, they also hold the status of a member of the Indonesian National Army (TNI), which carries distinct legal implications. This background leads to two main problems in this study: (1) the application of criminal law to military doctors, and (2) the forms of criminal liability for military doctors who commit offenses in the health sector. The research method used in this thesis is normative juridical. This thesis explores the legal liability of military doctors for criminal acts in the health sector. Based on the findings and discussions in this thesis, it is concluded that there are currently no specific regulations or laws governing the application of criminal law to military doctors. Consequently, military doctors who commit negligence or violations in the health sector are subject to the Criminal Code. If the crime breaches both general criminal law and special criminal law provisions, the military doctor will be subject to special criminal law. Keywords : Criminal Acts ; Criminal Responsibility ; Military Doctor.